Sequence Buster

Algebra Level 3

Given that { a n } \{a_{n}\} is a sequence satisfying a 0 a_{0} not equal to 0 0 or 1 1 , a 1 = 1 a 0 , a n + 1 = 1 a n ( 1 a n ) a_{1}=1-a_{0}, a_{n+1}=1-a_{n}(1-a_{n}) . Evaluate: a 0 a 1 a 2 a n ( 1 a 0 + 1 a 1 + 1 a 2 + + 1 a n ) a_{0}a_{1} a_2 \dotsm a_{n}\left(\frac{1}{a_{0}}+\frac{1}{a_{1}}+\frac 1{a_2}+ \dots +\frac{1}{a_{n}}\right) where n n is a positive integer


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Mark Hennings
Mar 24, 2020

Note that a n = 1 a n + 1 1 a n n 1 a_n \; = \; \frac{1-a_{n+1}}{1-a_n} \hspace{2cm} n \ge 1 so that n = 0 N a n = a 0 n = 1 N 1 a n + 1 1 a n = a 0 1 a N + 1 1 a 1 = 1 a N + 1 \prod_{n=0}^N a_n \; = \; a_0 \prod_{n=1}^N \frac{1-a_{n+1}}{1-a_n} \; = \; a_0 \frac{1 - a_{N+1}}{1-a_1} \; = \; 1 - a_{N+1} for all N 0 N \ge 0 . Also 1 1 a n + 1 1 1 a n = 1 a n ( 1 a n ) 1 1 a n = 1 a n n 1 \frac{1}{1-a_{n+1}} - \frac{1}{1-a_n} \; = \; \frac{1}{a_n(1-a_n)} - \frac{1}{1-a_n} \; = \; \frac{1}{a_n} \hspace{2cm} n \ge 1 so that n = 0 N 1 a n = 1 a 0 + n = 1 N ( 1 1 a n + 1 1 1 a n ) = 1 a 0 + 1 1 a N + 1 1 1 a 1 = 1 1 a N + 1 \sum_{n=0}^N \frac{1}{a_n} \; = \; \frac{1}{a_0} + \sum_{n=1}^N\left(\frac{1}{1-a_{n+1}} - \frac{1}{1-a_n}\right) \; = \; \frac{1}{a_0} + \frac{1}{1-a_{N+1}} - \frac{1}{1-a_1} \; = \; \frac{1}{1 - a_{N+1}} for all N 0 N \ge 0 , and hence n = 0 N a n × n = 0 N 1 a n = 1 \prod_{n=0}^Na_n \times \sum_{n=0}^N \frac{1}{a_n} \; = \; \boxed{1} for all N 0 N \ge 0 .

Superb solution!!!!

Mohammed Imran - 1 year, 2 months ago

You method of posting solutions are very admirable

Mohammed Imran - 1 year, 2 months ago
Cantdo Math
Apr 10, 2020

First inductively we can show, a n + 1 = 1 a 0 . a 1 . . . a n a_{n+1}=1-a_0.a_1...a_n Then we can inductively show, 0 n 1 a i = 1 a 0 . . . a n \sum_0^n \frac{1}{a_i} =\frac{1}{a_0...a_n} Hence ,the answer is 1.

Chew-Seong Cheong
Mar 25, 2020

From the first few a n a_n , we note that a n = 1 p n 1 a_n = 1 - p_{n-1} , where p n = k = 0 n a k p_n = \prod_{k=0}^n a_k . We can prove this claim by induction . For n = 1 n=1 , a 1 = 1 a 0 = 1 p 0 a_1 = 1-a_0 = 1-p_0 , the claim is true for n = 1 n=1 . Assuming the claim is true for n n , then

a n + 1 = 1 a n ( 1 a n ) = 1 a n ( 1 1 + p n 1 ) = 1 p n a_{n+1} = 1 - a_n(1-a_n) = 1-a_n(1-1+p_{n-1}) = 1-p_n

The claim is also true for n + 1 n+1 and hence true for all n 1 n \ge 1 .

We can also prove by induction that s n = k = 0 n 1 a k = 1 p n \displaystyle s_n = \sum_{k=0}^n \frac 1{a_k} = \frac 1{p_n} . For n = 1 n=1 , s 1 = 1 a 0 + 1 a 1 = a 1 + a 0 a 0 a 1 = 1 a 0 + a 0 p 1 = 1 p 1 s_1 = \dfrac 1{a_0} + \dfrac 1{a_1} = \dfrac {a_1+a_0}{a_0a_1} = \dfrac {1-a_0+a_0}{p_1} = \dfrac 1{p_1} . The claim is true for n = 1 n=1 . Assuming the claim is true for n n , then

s n + 1 = s n + 1 a n + 1 = a n + 1 + p n p n + 1 = 1 p n + p n p n + 1 = 1 p n + 1 s_{n+1} = s_n + \frac 1{a_{n+1}} = \frac {a_{n+1} + p_n}{p_{n+1}} = \frac {1-p_n+p_n}{p_{n+1}} = \frac 1{p_{n+1}}

The claim is also true for n + 1 n+1 and hence true for all n 1 n \ge 1 .

Therefore,

a 0 a 1 a 2 a n ( 1 a 0 + 1 a 1 + 1 a 2 + + 1 a n ) = p n ( 1 p n ) = 1 a_0a_1a_2\cdots a_n \left(\frac 1{a_0} + \frac 1{a_1} + \frac 1{a_2} + \cdots + \frac 1{a_n} \right) = p_n \left(\frac 1{p_n} \right) = \boxed 1

Superb solution

Mohammed Imran - 1 year, 2 months ago

Log in to reply

Glad that you like it.

Chew-Seong Cheong - 1 year, 2 months ago
Anand Raj
Mar 25, 2020

The solution provided by Mark Hennings is great, but I did something that I think I shouldn't have. So I'll share that here.

First, We write a 2 = 1 a 1 + a 1 2 = 1 ( 1 a 0 ) + ( 1 a 0 ) 2 = 1 a 0 + a 0 2 a_{2} = 1-a_{1}+{a_{1}}^{2} = 1-(1-a_{0})+{(1-a_{0})}^{2} = 1-a_{0}+{a_{0}}^2

Thus, a 0 a_{0} and a 1 a_{1} are cube roots of 1 -1 . That is a 0 = ω a_{0} = -\omega and a 1 = ω 2 a_{1} = -{\omega}^{2} , You can interchange them but it won't matter because in both cases a 2 = 0 a_{2} = 0 .

Thus all other a i = 1 a_{i} = 1 .

Since we need to find the sum of the products of these numbers taking all but one at a time, we can easily see that there is only one term that would be free of a 2 a_{2} , and that would be ω × ω 2 × 1 × . . . × 1 = 1 -\omega \times -{\omega}^{2} \times 1 \times ... \times 1 = \fbox{1}

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...